Development of smart parking system - Norbaiti Adzlina Basharudin (Universiti Malaysia Perlis, 2008)
The Development of Smart Parking System offers a simple and comprehensive solution to the problem of finding a convenient parking spot in large, multi-level parking garages. In an age where the adage ‘time is money’ seems more applicable than ever before, this user-friendly and adaptable system will eliminate the time drivers are forced to waste as they circle various parking garage floors looking for the optimal spot. The system itself consists of a user-interface at the entrance of the parking garage, which allows the parking attendance to view all available parking spaces. Although the system will recommend the spot it deems most favorable, the parking attendance is free to view each floor and select any available spot. Once a spot has been selected, a series of symbol built into the road will guide the parking attendance to their chosen destination. In addition, a ticket with directions will be printed that can be used upon return to the parking garage to guide the driver to their vehicle. The technical approach that I used for this project is a software system to produce a "proof of concept." I built a full graphical interface to simulate the actual software based system. This system and graphics are programmed using VB.NET. Interface is used to store the car number, time in, time out and parking amount. I accomplished everything that I set out and can confidently say that my project was a success.